A method for exfoliating AlGaN films from sapphire substrates using heated and pressurized water. (1st November 2022) - Matsubara, Eri; Hasegawa, Ryota; Nishibayashi, Toma; Yabutani, Ayumu; Yamada, Ryoya; Imoto, Yoshinori; Kondo, Ryosuke; Iwayama, Sho; Takeuchi, Tetsuya; Kamiyama, Satoshi; Shojiki, Kanako; Kumagai, Shinya; et al.
Abstract: Thin films of AlN, AlGaN, and AlGaN-based device structures of approximately 1 cm 2 formed on a sapphire substrate were successfully exfoliated from the substrate by immersion in heated (115 °C) and pressurized (170 kPa) water. These thin films were crystalline, grown on periodically formed AlN nanopillars. The water was permeated through intentional voids formed in the AlGaN or AlN crystalline layers by using periodic AlN nanopillars. The exfoliated AlGaN exhibited clear X-ray diffraction peaks from its (0002) plane diffraction. Transmission electron microscopy (TEM) confirmed that exfoliation introduced few additional dislocations and that the device structure was maintained.